2004
DOI: 10.1128/jb.186.5.1381-1387.2004
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the Interaction of Escherichia coli YjeQ with the Ribosome In Vitro

Abstract: Escherichia coli

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
168
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(187 citation statements)
references
References 15 publications
18
168
1
Order By: Relevance
“…2B). Previous work on RsgA from E. coli reported that the activity of the protein is increased in the presence of ribosomes (36,51). To determine the effect of ribosomes on the activity of all four GTPases, 70S ribosomes were purified from the community-acquired methicillin-resistant S. aureus (CA-MRSA) strain LAC* and included in the GTP hydrolysis assays.…”
Section: Resultsmentioning
confidence: 99%
“…2B). Previous work on RsgA from E. coli reported that the activity of the protein is increased in the presence of ribosomes (36,51). To determine the effect of ribosomes on the activity of all four GTPases, 70S ribosomes were purified from the community-acquired methicillin-resistant S. aureus (CA-MRSA) strain LAC* and included in the GTP hydrolysis assays.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies show that the GTPase activity of E. coli YjeQ, which associates with 30 S subunit, is enhanced in the presence of this subunit in vitro (25,26). Because YlqF bound to the free 50 S subunit, but not 30 S subunit, we next examined the activation of GTPase activity of YlqF by the 50 S subunit.…”
Section: Gtpase Activity Of Ylqf Is Stimulated By the 50 S Ribosomal mentioning
confidence: 99%
“…Another essential bacterial small GTP-binding protein, YjeQ, associates with the 30 S subunit in E. coli. Its GTPase activity is specifically enhanced in the presence of 30 S subunit (25,26). However, the precise actions of GTP-binding proteins on the ribosome remain to be clarified.…”
mentioning
confidence: 99%
“…A linear relationship was observed between the concentration of NS3-MBP and the amount of GTP hydrolyzed within 1 hr at 37° (Figure 3B), while the negative-control MBP protein was incapable of GTP hydrolysis. NS3's intrinsic GTP hydrolysis rate, K cat 4.27 6 0.59 min 21 , is on par with that of heterotrimeric G-proteins (K cat 3-5 min 21 ) (Kaziro et al 1991), although relatively high compared to some circularly permuted GTPases (K cat 0.2 min 21 ) (Daigle and Brown 2004;Himeno et al 2004;Bassler et al 2006;Cladiere et al 2006) and canonical Ras and Rab GTPase members (K cat ,0.01 min 21 ) (Kaziro et al 1991). It is unknown whether GTPase activities of Lsg1/NS3 orthologs can be stimulated by GTPase-activating proteins (GAPs) or other factors that can increase catalytic rate .100-fold (Kaziro et al 1991;Bernards and Settleman 2004).…”
Section: Ns3 Is a Functioning Gtpase And Inactivation Of This Domain mentioning
confidence: 97%
“…It is unknown whether GTPase activities of Lsg1/NS3 orthologs can be stimulated by GTPase-activating proteins (GAPs) or other factors that can increase catalytic rate .100-fold (Kaziro et al 1991;Bernards and Settleman 2004). For instance, the K cat of E. coli YRG member YjeQ is increased 500-fold in the presence of small ribosomal subunits (Daigle and Brown 2004).…”
Section: Ns3 Is a Functioning Gtpase And Inactivation Of This Domain mentioning
confidence: 99%